Analisis Kesulitan Siswa Kelas II Sekolah Dasar dalam Menyelesaikan Soal Pemecahan Masalah Matematika Materi Perkalian dan Pembagian - sisca; Fajar Cahyadi; Husni Wakhyudin (Jurnal Gentala Pendidikan Dasar, 2020)
One of the competencies that students must master in learning mathematics is to perform addition, subtraction, multiplication, division and mixed operations, including those involving fractions. So, students can solve problems which include the ability to understand problems, design mathematical models, solve models, and interpret the solutions obtained. The purpose of this study was to determine the types of errors made by students, to describe the students' abilities, and to determine the factors that caused students of Class IIA SDN Pandeanlamper 05 Semarang to experience difficulties in solving math problem solving problems. The research method used is descriptive qualitative research methods. The subjects of this study were 25 students of Class IIA SDN Pandeanlamper 05 Semarang. After being analyzed, the results obtained were that students had difficulty solving problems solving math problems with the material of multiplication and division, namely 1) Students did not understand the meaning or content of story problems, 2) The students' ability to memorize multiplication and division was still low, 3) External factors such as health conditions, socioeconomic status, and student attendance have an effect on students' ability to solve math problem solving problems. This proves that the difficulties experienced by students in solving math problem solving problems are caused by two factors, namely internal factors and external factors.